The hidden kingdom - Sutherland, Tui T. (Wings of fire, 2013)
The dragonets of destiny aren't sure what to expect in the RainWing kingdom - Glory hopes to learn more about her family, and since the RainWings aren't fighting in the war, all five dragonets think they might be able to hide safely for a while. But something deadly is stalking the peaceful kingdom, and the dragonets soon discover that RainWings have been mysteriously disappearing from the forest. When the RainWing queen won't do anything to find her missing tribe members, Glory and her friends set off on their own rescue mission - which leads them right back into enemy territory...